RETRACTED: CMTM6 as a candidate risk gene for cervical cancer: Comprehensive bioinformatics study - Huang, Xiaoting; Liu, Wei; Liu, Chunshan; Hu, Jijie; Wang, Baiyao; Ren, Anbang; Huang, Xiaona; Yuan, Yawei; Liu, Jinquan; Li, Mingyi (Frontiers in Molecular Biosciences, 2022)
Background: CKLF like MARVEL transmembrane domain containing 6 (CMTM6) is an important programmed cell death 1 ligand 1 regulator (PD-L1). CMTM6 was reported as an important regulator of PD-L1 by promoting PD-L1 expression in tumor cells against T cells. However, the function of CMTM6 in cervical cancer is not well characterized. In addition, the role of CMTM6 in the induction of epithelial-mesenchymal transition (EMT) in the context of cervical cancer is unknown. Methods: In this study, we evaluated the role of CMTM6, including gene expression analysis, miRNA target regulation, and methylation characteristic, using multiple bioinformatics tools based on The Cancer Genome Atlas (TCGA) database. The expression of CMTM6 in cervical cancer tissues and non-cancerous adjacent tissues was assessed using immunohistochemistry. In vitro and in vivo function experiments were performed to explore the effects of CMTM6 on growth and metastasis of cervical cancer. Results: Human cervical cancer tissues showed higher expression of CMTM6 than the adjacent non-cancerous tissues. In vitro assays showed that CMTM6 promoted cervical cancer cell invasion, migration, proliferation, and EMT via activation of mitogen-activated protein kinase (MAPK) c-jun N-terminal kinase (JNK)/p38 signaling pathway. We identified transcription factors (TFs), miRNAs, and immune cells that may interact with CMTM6. Conclusions: These results indicate that CMTM6 is a potential therapeutic target in the context of cervical cancer.